The optimal cryo revival period of cryopreserved Wharton’s jelly derived-mesenchymal stem cells - Vikneswary Ravi Kumar; Mohamad Fikeri Ishak; Sharifah Izwan Tuan Othman; Tristan, Tan; Yogeswaran Lokanathan (Penerbit Universiti Kebangsaan Malaysia, 2023)
The workflow of cryopreservation is a challenging step in the standardised preparation of cell therapy products in terms of methods used (i.e., adapted controls of the work environment, quality control, reagents, and equipment). This study aimed to determine the effect of cryopreservation on the stability of mesenchymal stem cell (MSC) characteristics by comparing fresh cells with those that underwent different post-thaw cell recovery periods. The MSCs were derived from human Wharton’s jelly umbilical cord (n = 4). The cells that were cryopreserved for 7 days were revived at 0 h (CRC-0h), 24 h (CRC-24h) and 7 days (CRC-7d) and then evaluated on the basis of cell viability, doubling time, morphology, trilineage differentiation potential, growth kinetics, and MSC surface marker expression. The cell viability of the CRC-0h group was 90%, whereas that of the CRC-24h group was 80%-85%. Cell attachment results showed that CRC-24h had a notably higher attachment rate than the other two groups. The CRC groups showed CD90, CD73 or CD44 expression, which meets the minimum criteria for defining multipotent MSCs. By contrast, CD105 expression was significantly reduced in the CRC groups and was lower than the minimum requirement based on the standards of the International Society for Cellular Therapy. Results suggest that at least 24 h is necessary to improve the quality of MSCs for it to be adequate for cell therapy use.